Paralichthys patagonicus spawning areas and reproductive potential in the Bonaerense Coastal Zone, Argentina (34º-42ºS) - Militelli, Maria Ines (2011)
Paralichthys patagonicus reproductive biology was studied using macroscopic and histological analysis of gonads in waters of Argentinean Coastal Zone (34º-42ºS) during December 2003 and 2005. Data were analyzed taking into account two population groups, one in the northern zone (34º-38ºS) and another in El Rincón (38º-42ºS). The size at first maturity (L50) estimated P. Patagonicus showed differences between years and populations groups. The size at first maturity for both sexes in 2003 was 31.57 cm TL for the northern zone and 29.58 cm TL for El Rincon. In 2005 it was only able to estimate the L50 to the northern zone and the value obtained was less than 2003 (27.82 cm TL). During December 2003 most of hydrated or ripe females were detected within El Rincón. However, in December 2005 the highest proportion of spawning females was observed in the external sector of the Rio de la Plata, possibly due to the colder temperatures observed in the northern area relative to 2003. Batch fecundity was fitted to a power function of length and linear function of ovary free female weight and ranged from 14,685 (30 cm TL) to 153,717 (59 cm TL) hydrated oocytes. Relative fecundity oscillated between 24 and 170 hydrated oocytes/g. The values these parameters differed between years and among population groups. These differences could be attributed in part to the difference in seawater temperature between the two years, especially at high temperatures observed in 2005